LEADERSHIP COMPETENCY DEVELOPMENT STRATEGIES FOR SENIOR-LEVEL CIVIL SERVANTS AT INAP TIMOR-LESTE - Celesta Fernandes Pinto; Mala Sondang Selitonga (Fakultas Keguruan Dan Ilmu Pendidikan Universaitas PGRI Banyuwangi, 2026)
This study aims to describe the strategies for developing leadership competencies at the senior level within INAP Timor-Leste, using the theoretical framework of competency development and human resource development. The research employs a descriptive qualitative approach, involving informants from policy-making, implementation, and evaluation bodies responsible for the development of leadership competencies for senior-level civil servants at INAP Timor-Leste and the Civil Service Commission of Timor-Leste. The findings indicate that the development of leadership competencies for senior-level civil servants has not been optimal. This is due to development designs still relying on outdated needs analyses that no longer address current demands, continued dependence on an old curriculum, limitations in resources (trainers, facilities and infrastructure, as well as technological and digital infrastructure), weak leadership commitment in policy implementation, and learning methods that remain largely confined to classical approaches. Additionally, there is a policy gap concerning the regulation of leadership competency development, particularly related to Decreto Lei do Governo No. 7/2024, the first amendment to Decreto Lei do Governo No. 7/2024. Therefore, strategies to optimize leadership competency development at the senior level in INAP include conducting updated needs analyses to design demand-based programs, strengthening resources (trainers, facilities, infrastructure, and digital technology), developing more varied learning methods, and reinforcing policies governing leadership competency development.